2023
DOI: 10.1186/s41984-023-00190-4
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective epidemiological study of the World Health Organization (WHO)-classified primary brain and other Central Nervous System (CNS) tumors from a tertiary health care center in Northeast India

Abstract: Background Brain and other central nervous systems (CNS) tumors are a heterogeneous group of neoplasms that are prevalent in all age groups and gender. The study aimed to investigate the pattern of distribution of World Health Organization (WHO) classified primary brain and other CNS tumors among different age groups and gender at a tertiary care center in Northeast India. This is the first study of CNS tumors from this region of the country. The data obtained can be useful for correct diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…No significant differences in age groups between the males and females were found (p-value = 0.352). The distribution of the percentage of patients in the age groups was similar to the findings reported in a study in Northeast India and Qatar [ 18 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…No significant differences in age groups between the males and females were found (p-value = 0.352). The distribution of the percentage of patients in the age groups was similar to the findings reported in a study in Northeast India and Qatar [ 18 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…Meningiomas were the most common group of tumors identified in different studies around the world, including the USA (42.1%) [ 14 ], Korea (37.9%) [ 20 ], Lebanon (29.6%) [ 17 ], Northeast India [ 25 ], and Georgia [ 23 ], while in our study, the most common group of tumors identified in Palestinian adolescents and adults was diffuse astrocytic and oligodendroglial tumors (33%). In our study, the most commonly identified histopathological type was glioblastoma, while meningioma was the most common histopathological type identified in the USA [ 14 ], Korea [ 20 ], Jordan [ 6 ], Cameroon [ 27 ], and Austria [ 21 ].…”
Section: Discussionmentioning
confidence: 45%